FEATURES OF DEVELOPMENT OF INTERNATIONAL LEASING IN ECONOMY OF FOREIGN COUNTRIES - V. Vesina (Вестник университета)
The article is devoted to theoretical aspects of the analysis of evolution and stages of establishment of international leasing in economy of foreign counties. The role of renting and scientific and technical progress in mechanism forming of international leasing is shown. Presents periodization of the stages of establishment of international leasing in global economy.